A new supernumerary tooth occurring in the same region during follow-up after supernumerary tooth extraction: A case report. Issue 1 (April 2021) - Akitomo, Tatsuya; Asao, Yuria; Mitsuhata, Chieko; Kozai, Katsuyuki
Abstract: A supernumerary tooth (ST) is often detected in the childhood and a surgical approach is usually indicated for its management. Some cases may require orthodontic treatment after extraction; hence, a long-term follow-up is important. A 4-year-and-11-month-old Japanese boy was referred to our hospital for dental caries treatment. A radiographic examination at 5 years and 5 months revealed an ST near the maxillary left primary central incisor, which was later extracted. One year and 6 months after extraction, a metachronous new ST in the same region was detected. We highlight the importance of a regular radiographic examination after ST extraction.